Oleate induces KATP channel-dependent hyperpolarization in mouse hypothalamic glucose-excited neurons without altering cellular energy charge. (27th March 2017) - Dadak, Selma; Beall, Craig; Vlachaki Walker, Julia M.; Soutar, Marc P.M.; McCrimmon, Rory J.; Ashford, Michael L.J.
Highlights: Oleate and low glucose hyperpolarize and inhibit GT1-7 and mouse GE neurons by activation of KATP . Oleate inhibition of GT1-7 neuron activity is not mediated by AMPK or fatty acid oxidation. Activation of KATP by oleate requires ATP hydrolysis but does not reduce the levels ATP or the ATP:ADP ratio. GT1-7 hyperpolarization by oleate is not dependent on UCP2. Oleate and low glucose depolarize a subpopulation of hypothalamic GI neurons. Abstract: The unsaturated fatty acid, oleate exhibits anorexigenic properties reducing food intake and hepatic glucose output. However, its mechanism of action in the hypothalamus has not been fully determined. This study investigated the effects of oleate and glucose on GT1-7 mouse hypothalamic cells (a model of glucose-excited (GE) neurons) and mouse arcuate nucleus (ARC) neurons. Whole-cell and perforated patch-clamp recordings, immunoblotting and cell energy status measures were used to investigate oleate- and glucose-sensing properties of mouse hypothalamic neurons. Oleate or lowered glucose concentration caused hyperpolarization and inhibition of firing of GT1-7 cells by the activation of ATP-sensitive K + channels (KATP ). This effect of oleate was not dependent on fatty acid oxidation or raised AMP-activated protein kinase activity or prevented by the presence of the UCP2 inhibitor genipin. Oleate did not alter intracellular calcium, indicating that CD36/fatty acid translocase may not play a role. However, oleate activation of KATP may require ATP metabolism. The short-chain fatty acid octanoate was unable to replicate the actions of oleate on GT1-7 cells. Although oleate decreased GT1-7 cell mitochondrial membrane potential there was no change in total cellular ATP or ATP/ADP ratios. Perforated patch and whole-cell recordings from mouse hypothalamic slices demonstrated that oleate hyperpolarized a subpopulation of ARC GE neurons by KATP activation. Additionally, in a separate small population of ARC neurons, oleate application or lowered glucose concentration caused membrane depolarization. In conclusion, oleate induces KATP- dependent hyperpolarization and inhibition of firing of a subgroup of GE hypothalamic neurons without altering cellular energy charge.